The Skandapurāṇa Volume IIb Adhyāyas 31-52. The Vāhana and Naraka Cycles - Bakker, Hans T.; Bisschop, Peter C.; Yokochi, Yuko (Groningen Oriental Studies, Supplement, 2014)
Skandapurāṇa IIb presents a critical edition of Adhyāyas 31-52 from the Skandapurāṇa, with an introduction and English synopsis. ; Readership: All interested in Sanskrit literature, Purana literature, early Saivism, Hindu mythology, and the history of Hinduism in general.